Evaluation of Flood and Drought Events Using AR5 Climate Change Scenarios in Indonesia - M. Faisi Ikhwali; Maulana Ibrahim Rau; Benazir; Chalermchai Pawattana; Husnawati Yahya (Journal of the Civil Engineering Forum, 2023)
Indonesia is an archipelagic country located on the equator. The issue of climate change has become a global issue that has impacted several sectors in Indonesia recently. The presence of the Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) has contributed to conducting studies on flood and drought events. This review paper summarized 16 published papers that have gone through peer-review, both in the form of publications in journals and at conferences. Since the release of the IPCC AR5 to date, ten studies on flooding and six studies on drought events have been conducted. The most publications on this in 2019 were five publications. Of the various types of the Representative Concentration Pathway (RCP) scenarios used with various methods, the most widely used scenario RCPs is RCP4.5. From the climate change scenario, precipitations parameter is the main parameter that is used in assessing flood or drought events. There are studies conducted on a district / city, provincial scale, and some are even carried out on a watershed scale. The location or province that most flood studies have been carried out is in the capital of Jakarta. The results of these studies generally indicate that the incidence of floods and droughts will increase in the future. Therefore, adaptation steps are needed to deal with unfavorable conditions in the future. Moreover, as the capital city, Jakarta has been estimated that the projected flood incidence will increase. Several publications have provided steps to deal with these challenges on the positive side.